2021
DOI: 10.1007/s00167-021-06557-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review evaluating the clinimetric properties of the Victorian Institute of Sport Assessment (VISA) questionnaires for lower limb tendinopathy shows moderate to high-quality evidence for sufficient reliability, validity and responsiveness—part II

Abstract: Purpose The evaluation of measurement properties such as reliability, measurement error, construct validity, and responsiveness provides information on the quality of the scale as a whole, rather than on an item level. We aimed to synthesize the measurement properties referring to reliability, measurement error, construct validity, and responsiveness of the Victorian Institute of Sport Assessment questionnaires (Achilles tendon—VISA-A, greater trochanteric pain syndrome—VISA-G, proximal hamstring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 65 publications
(194 reference statements)
0
39
0
Order By: Relevance
“…In essence, shortcomings as those highlighted in recent years concerning the VISA-A [3,11], most likely apply to all VISA questionnaires, as also indicated by our recent systematic reviews in this journal from 2021 [8,9]. Beyond the obvious evidence and the appraisal of measurement bonafides of VISA from these reviews, the questionnaires incorporate complex items with complicated scoring and thematic ambiguity [3] that needs reconsideration.…”
Section: Current Visas-expired Time For Renewal!mentioning
confidence: 98%
See 2 more Smart Citations
“…In essence, shortcomings as those highlighted in recent years concerning the VISA-A [3,11], most likely apply to all VISA questionnaires, as also indicated by our recent systematic reviews in this journal from 2021 [8,9]. Beyond the obvious evidence and the appraisal of measurement bonafides of VISA from these reviews, the questionnaires incorporate complex items with complicated scoring and thematic ambiguity [3] that needs reconsideration.…”
Section: Current Visas-expired Time For Renewal!mentioning
confidence: 98%
“…Although our systematic review revealed high-quality evidence for sufficient construct validity of all VISA questionnaires, some general limitations to their construct validity remain. None of the VISA development studies predetermined the expected direction and magnitude of the correlations with the comparator instruments [2,5,15,19], and the majority of the VISA questionnaires validation studies just modelled their methodology based upon the approach of previous studies [8,9] without any underlying theoretical concept and hypotheses testing. From an in-depth inspection of study methods assessing validity of the VISA questionnaires, 82% of these studies used comparator scales without proven reliability and/or validity, or using non condition-or region-specific PROMs [8,9].…”
Section: Construct Validity-concept and Hypotheses Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The suitability of two items in the VISA questionnaires for less active populations has come under scrutiny, due to the focus on the performance of sporting activities (item seven and eight) 31–33. For example, in item eight of VISA-G responders are asked to answer one of three sections that corresponds with their ability to perform activities for certain durations, and consider the influence on pain in the performance of the activity 21.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-season evaluation consisted of measuring the isokinetic knee strength and performing single-leg CMJ and one-leg hop tests in random order. Moreover, the volleyball players' symptoms and their sportive activities were assessed by the Victorian Institute of Sport Assessment-Patella (VISA-P) score [20], which is a reliable and valid tool [21]. Every player received standardized information and a demonstration of the jumps.…”
Section: Participants and Recruitmentmentioning
confidence: 99%